Research on the bioactivity of isoquercetin extracted from marestail on bladder cancer EJ cell and the mechanism of its occurrence. (2nd April 2016) - Ran, Juhong; Wang, Yanping; Zhang, Wei; Ma, Minyu; Zhang, Haiying
Abstract : Research studies in recent years have found that isoquercetin has an inhibiting effect on multiple carcinogens, but research studies filed on isoquercetin in bladder cancer are quite few. This paper observed the influence of isoquercetin on biological activity of the EJ cell of bladder cancer through HC dyeing and trypan blue counting, studied the EJ cell cycle by flow cytometry (FCM), and then analyzed the influence of isoquercetin and its effect on the protein expression of STAT3 and STAT3-inhibiting factors (PIAS3) in EJ cells. Research has shown that isoquercetin has an inhibitory effect on the EJ cells of bladder cancer, but it is not obvious.